2002
DOI: 10.1002/bit.10150
|View full text |Cite
|
Sign up to set email alerts
|

Direct transesterification of gases by “dry” immobilized lipase

Abstract: Several different reactor configurations, including single pass, continuous recycle, and batch reactor modes, were used to investigate the effects of temperature and water activity, or relative humidity, on lipase-catalyzed, gas-phase transesterifications. Temperature and relative humidity were controlled both inside reactors and throughout the course of the reaction to account for and optimize their effects. Results indicated that, at low relative humidity, reaction rates increased with temperature up to 60 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
4
11
0
Order By: Relevance
“…A mass balance performed on the reactants revealed that the molar yield of acetic acid accounted for about 6-13% of the initial propanol concentration depending on the temperature. Similar results were reported with vinyl acetate/isoamyl acetate transesterification [21]. Fig.…”
Section: Transesterification Between Vinyl Acetate and N-propanol Catsupporting
confidence: 90%
See 1 more Smart Citation
“…A mass balance performed on the reactants revealed that the molar yield of acetic acid accounted for about 6-13% of the initial propanol concentration depending on the temperature. Similar results were reported with vinyl acetate/isoamyl acetate transesterification [21]. Fig.…”
Section: Transesterification Between Vinyl Acetate and N-propanol Catsupporting
confidence: 90%
“…Therefore, initial substrate concentrations varied when changing the temperature or H R and comparison on the basis of initial rates was not possible [21]. As a result, all reaction rates were measured under steady-state conditions.…”
Section: Effect Of Temperature and Relative Humidity On Ethyl Acetatementioning
confidence: 99%
“…As with the study by Cameron et al (2002), a significant amount of activity, determined from initial rate measurements, was seen at a RH equal to zero. The rate of reaction was then seen to decrease with increasing water activity, as shown in figure 14.…”
Section: Gas-phase Dry Enzyme Activity Resultssupporting
confidence: 70%
“…As noted by the authors, explaining this behaviour is difficult as the exact distribution of the water between the support and the enzyme is unknown. Cameron et al (2002) also studied the effect of water activity on the rate of transesterification by porcine pancreatic lipase. The enzyme was immobilized on glass wool that was then used in reactors of various configurations.…”
Section: Gas-phase Dry Enzyme Activity Resultsmentioning
confidence: 99%
“…ESI has previously been demonstrated to generate intact non-covalent complexes in the gas phase [5,6] and empty virus particles have been successfully mass measured [7]. Specifically, hapten binding by an antibody [8], stability of protein conformers [9] and enzymatic activity [10] in the gas phase all suggest that the native fold of a protein can be retained. It should be noted that gas phase binding affinities [11] and the distribution of folding intermediates [12] can differ from the solution conformation.…”
Section: Introductionmentioning
confidence: 99%